Mechanisms of DNA damage response to targeted irradiation in organotypic 3D skin cultures. - Anna Acheva (PLoS ONE, 2014)
DNA damage (caused by direct cellular exposure and bystander signaling) and the complex pathways involved in its repair are critical events underpinning cellular and tissue response following radiation exposures. There are limited data addressing the dynamics of DNA damage induction and repair in the skin particularly in areas not directly exposed. Here we investigate the mechanisms regulating DNA damage, repair, intracellular signalling and their impact on premature differentiation and development of inflammatory-like response in the irradiated and surrounding areas of a 3D organotypic skin model. Following localized low-LET irradiation (225 kVp X-rays), low levels of 53BP1 foci were observed in the 3D model (3.8±0.28 foci/Gy/cell) with foci persisting and increasing in size up to 48 h post irradiation. In contrast, in cell monolayers 14.2±0.6 foci/Gy/cell and biphasic repair kinetics with repair completed before 24 h was observed. These differences are linked to differences in cellular status with variable level of p21 driving apoptotic signalling in 2D and accelerated differentiation in both the directly irradiated and bystander areas of the 3D model. The signalling pathways utilized by irradiated keratinocytes to induce DNA damage in non-exposed areas of the skin involved the NF-κB transcription factor and its downstream target COX-2.